Strategi Pengembangan Kompetensi Pegawai Negeri Sipil di Kepolisian Daerah Metro Jaya - Puspitaningrum, Windhy; Hamka, Hamka; Sutrisno, Edy (Universitas Batanghari Jambi, 2024)
The research was carried out with the aim of finding out the factors that cause the development of civil servant competencies to not be optimal and strategies that can optimize the competency development of civil servants. This research uses a qualitative approach. Data collection was obtained through data examination and interviews with sources related to competency and development. The locus of this research is Polda Metro Jaya. The research results show that the implementation of development has not been optimal. This can be seen from the fact that only a few personnel participate in competency development. Apart from that, personnel were found who did not have competence, but held positions. The lack of optimal competency development is divided into supporting factors and inhibiting factors. The suggestion from this research is to develop a strategy that can optimize competency development by maximizing supporting factors and overcoming inhibiting factors in competency development.